To add \(3.2 \times 10^4\) and \(1.95 \times 10^6\), we should first express both numbers in the same power of ten.
In this case, we can convert \(3.2 \times 10^4\) to the same exponent as \(1.95 \times 10^6\).
Convert \(3.2 \times 10^4\) to the form of \(10^6\):
\[ 3.2 \times 10^4 = 3.2 \times 10^4 \times \frac{10^2}{10^2} = 3.2 \times \frac{10^6}{10^2} = \frac{3.2}{100} \times 10^6 = 0.032 \times 10^6 \]
Now, we can add this to \(1.95 \times 10^6\):
\[ 0.032 \times 10^6 + 1.95 \times 10^6 = (0.032 + 1.95) \times 10^6 = 1.982 \times 10^6 \]
So, the result of adding \(3.2 \times 10^4\) and \(1.95 \times 10^6\) indeed equals \(1.982 \times 10^6\).
Thus, the equation \(3.2 \times 10^4 + 1.95 \times 10^6 = 1.982 \times 10^6\) is correct.